Use of rapid light curves to evaluate photosynthetic changes in turfgrasses exposed to low‐light conditions. Issue 1 (21st April 2021) - Jespersen, David; Xiao, Bo
Abstract: Shade is a widespread issue for turf areas that reduces turf quality, and the lack of light to drive photosynthetic processes is one major factor responsible for these declines. Maintaining a positive carbon balance is essential for plant survival under low‐light conditions, but large‐scale screening for photosynthetic performance can be a difficult task. Chlorophyll fluorescence rapid light curves (RLC) were used to understand difference in photosynthetic processes of hybrid bermudagrass 'Tifway' ( Cynodon dactylon (L, ) Pers. × C. transvaalensis Burtt Davy) and Japanese lawngrass 'El Toro' ( Zoysia japonica Steud.) to high‐light (800 µmol m –2 s –1 ) and low‐light (200 µmol m –2 s –1 ) treatments in controlled environment studies. Measurement of maximum potential quantum yield (Fv/Fm) did not change over the course of the study but were significantly greater in El Toro. Tifway grown under high‐light treatment had greater maximum photosynthesis, and dark respiration rates compared to El Toro. The RLCs demonstrated that compared to hybrid bermudagrass in the low‐light treatment, Japanese lawngrass was more efficient at harvesting light at lower irradiance levels, but also reached saturation of light harvesting at lower irradiance levels. Differences in rapid light curves among plants grown under high‐light or low‐light treatments may be due to differences in photoacclimation. While rapid light curves should not be seen as a replacement for traditional light response curves based on CO2 flux, they did provide valuable information about acclimation of photosynthetic systems and warrant further testing in real‐world conditions. Core Ideas: Low‐light intensity is a major stress affecting turfgrass performance Chlorophyll fluorescence is a tool that can provide information on photosynthetic processes Rapid light curves (RLC) were able to detect differences among turfgrass species